Influence on Therapeutic Decision-Making of Supine and Standing Radiographs after Traumatic Thoracolumbar Fracture in the Elderly - Noguera-Alonso, Laura; Vilà-Canet, Gemma; De Caso-Rodriguez, Julio; Da Ponte-Prieto, Ariadna; Perez-Romera, Ana Belen; Velazquez-Fragoso, Juan Jose (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background A standing X-ray is recommended for decision-making relative to the therapy for a traumatic thoracolumbar fracture (TLF). However, standing X-ray management can be demanding in elderly patients because of pain. The goal of this study was to determine whether supine radiograph is sufficient for proper therapeutic decision-making in patients older than 65 years with acute stable traumatic TLF.Methods Patients older than 65 years who came to the emergency department diagnosed with an acute and stable traumatic vertebral fracture between T10 and L3 (both included) were included in the study. Initially, all the patients were studied with a supine radiograph and computed tomography (CT) scan. If the TLF was stable, a standing radiograph was performed. Segmental kyphosis (SK) and visual analog scale (VAS) score were collected and compared in both the supine and standing X-ray projections.Results Twenty-seven patients with a mean age of 76.39 (range: 65–93) years were included; most were females. The mean supine SK was 10.14degrees (SD±7.22degrees). It increased to 12.97 (SD±8.61degrees) in the standing projection (p<0.001). In 37.1% of the patients, the SK increased from 13.22degrees (SD±7.21degrees) in supine X-ray to 19.96degrees (SD±5.34degrees) in the standing position in this group. When the initial supine projection showed an SK of ≥10degrees, the mean SK observed in the standing X-ray increased to 20.5degrees (SD±5.30, p=0.321).Conclusion Stable traumatic TLF in patients older than 65 years showing ≥10degrees of SK in supine radiography may benefit from a standing radiography to make a proper therapeutic decision.
Keywords: stable; thoracolumbar; fracture; standing; radiograph